Sputum Sample Quality and Delay of TCM Examination and Microscopic Results from Tuberculosis Suspect Patient - Yusianti Silviani; Ardy Prian Nirwana; Didik Wahyudi (Jurnal Media Analis Kesehatan, 2023)
Tuberculosis (TB) is a disease with a mortality rate equivalent to 11 deaths/hour caused by Mycobacterium tuberculosis. Technological developments have been able to detect TB with the GeneXpert® MTB/RIF TCM (Rapid Molecular Test) examination. The aim of this study was to determine the effect of sputum sample quality and examination delays on TCM and microscopic results in patients suspected of having tuberculosis. The research design used in this study used experimental analytics with a cross-sectional approach. The sample in this study was 40 samples taken using quota sampling. Samples were examined using Microscopic and TCM methods. In the microscopic method, 3 treatment delays are carried out, namely immediately, 5 hours and 24 hours. The results showed that all samples experienced a decrease in the number of BTA + but a decrease in grade did not occur in all samples. The decrease in consistency began to appear at a delay of 5 hours. A decrease in BTA microscopic grading often occurs when the delay is from 5 hours to 24 hours. From the results of the Friedman test, a value of α= 0.000 (< 0.05) was obtained so that it can be concluded that there is no difference in the results of microscopic examination with TCM, but there is an influence of sputum quality on BTA results (+) and there is an influence of delay time on microscopic examination of BTA.